2009
DOI: 10.1007/s00280-009-1150-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit from ovarian metastatectomy in colorectal cancer patients with ovarian metastasis: a retrospective analysis

Abstract: Based on this retrospective analysis, the ovarian metastatectomy significantly prolonged survival in CRC patients with ovarian metastases. The potential role of an ovarian metastatectomy in the management of CRC should be prospectively studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 14 publications
6
62
1
Order By: Relevance
“…In spite of such progress, the prognosis of patients with ovarian metastases from CRC remains poorer than that of other metastatic sites [7][8][9]. The incidence of ovarian metastases from CRC is rare and estimated to be 3-14% [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of such progress, the prognosis of patients with ovarian metastases from CRC remains poorer than that of other metastatic sites [7][8][9]. The incidence of ovarian metastases from CRC is rare and estimated to be 3-14% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, large ovarian metastases are often symptomatic and decrease a patient's quality of life (QOL). Although it has been retrospectively suggested that the surgical resection of ovarian metastases may contribute to an improvement in survival and QOL [7], the prognosis of patients with ovarian metastases from CRC, especially with ex-ova metastases, was still dismal with median survival times reported to be 10-20 months, even after surgical resection with systemic CTx [8,9]. Thus, an optimal treatment strategy for ovarian metastases from CRC needs to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Neoplastic cells of colorectal origin are quite known to attack the ovaries, so much so that they are commonly referred to as a “sanctuary site” [2].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ovarian metastases (Krukenberg tumor), however, is not as precise. In fact, in literature, the gap ranges from 1.2% and 30.8%, with synchronous metastases (1.3–10%) being more prevalent than those metachronous (1.3–2.4%) [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, synchronous OM are reported in 1-9 % of the women undergoing surgical resection of a primary CRC, and metachronous OM occur in only 1-7 %. [2][3][4][5] In cases of peritoneal carcinomatosis, more than half of the women have OM diagnosed either before or synchronously. 6 In recent years, the survival of patients with colorectal peritoneal carcinomatosis (CRPC) has improved as a result of multimodal treatment combining surgical complete cytoreduction (CRS) and intraperitoneal chemotherapy (IPC).…”
mentioning
confidence: 99%